2008
DOI: 10.1016/j.visres.2007.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Aging disrupts the neural transformations that link facial identity across views

Abstract: Healthy human aging can have adverse effects on cortical function and on the brain's ability to integrate visual information to form complex representations. Facial identification is crucial to successful social discourse, and yet, it remains unclear whether the neuronal mechanisms underlying face perception per se, and the speed with which they process information, change with age. We present face images whose discrimination relies strictly on the shape and geometry of a face at various stimulus durations. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
75
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(87 citation statements)
references
References 42 publications
12
75
0
Order By: Relevance
“…As such, the results from Experiment 1 confirm previously reported findings that face matching performance de clines with age (e.g., Grady et al, 2000) and that this age-related cost is particularly apparent when matching facial identity across novel views of the face (Habak, Wilkinson, & Wilson, 2008). However, although older adults were overall worse at matching identity we noted that the cost on identity matching across views, which has previously been reported to be exacerbated by the ageing process, was evident only when the target face was pre sented as a sequence of three static images containing rigid changes (i.e., head rotation).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…As such, the results from Experiment 1 confirm previously reported findings that face matching performance de clines with age (e.g., Grady et al, 2000) and that this age-related cost is particularly apparent when matching facial identity across novel views of the face (Habak, Wilkinson, & Wilson, 2008). However, although older adults were overall worse at matching identity we noted that the cost on identity matching across views, which has previously been reported to be exacerbated by the ageing process, was evident only when the target face was pre sented as a sequence of three static images containing rigid changes (i.e., head rotation).…”
Section: Discussionsupporting
confidence: 88%
“…However, activation in this network was not suf ficient to support the matching of identity across views, as older adults who engaged this network did not reliably exhibit faster response times in this condition. Consistent with the conclusions drawn by Habak et al (2008), the results observed by Lee et al suggest that the ability to represent facial identity across different views diminishes with age and that this performance decrease likely emerges due to functional changes in the face processing network.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…[21][22][23] Age-related differences exist in the perception of shapes defined by texture, 24 and for higher levels of form processing, such as facial matching when faces are displayed from different viewpoints. 25 Previous studies that have documented age-related changes to form perception generally have included two age groups: younger adults (usually below ages 35 to 40 years) and older adults (typically over the age of 60 years), and have conducted detailed experiments on a specific aspect of form perception (e.g., orientation discrimination, 12 center-surround suppression of perceived contrast, 18,19 contour integration, 22 shape discrimination 26 ). Differing experimental designs among studies limit the ability to compare the relative magnitude of agerelated change across the many different aspects of form perception.…”
mentioning
confidence: 99%